2009
DOI: 10.1037/a0013722
|View full text |Cite
|
Sign up to set email alerts
|

Do pigeons (Columba livia) study for a test?

Abstract: In 4 experiments, the authors asked whether pigeons (Columba livia) would show metamemory by choosing to study a sample stimulus before taking a memory test. In Experiments 1a-1c, pigeons chose between cues that led either to exposure to a sample stimulus or directly to the comparison test stimuli without seeing the sample in a delayed matching-to-sample task. The same choice was used in Experiment 2 to see whether pigeons would take a reminder when memory of the sample was weak. In Experiments 3 and 4, pigeon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
100
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(105 citation statements)
references
References 20 publications
(33 reference statements)
2
100
0
1
Order By: Relevance
“…Rats (Foote & Crystal, 2007 and birds (Goto & Watanabe, 2012;Inman & Shettleworth, 1999;Roberts et al 2009;Teller, 1989) have provided inconclusive evidence supporting a claim of metacognitive abilities in some experiments. In other experiments, rats (Kirk, McMillan, & Roberts, 2014;Templer, Lee, & Preston, 2017) and birds (Castro & Wasserman, 2013;Roberts, McMillan, Musolino, & Cole, 2012;Watanabe & Clayton, 2016) do appear to show responding consistent with a hypothesis of influence by a metacognitive system using the information-seeking paradigm or an uncertainty response.…”
Section: Limited Success In Metacognition Tests In Non-primate Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Rats (Foote & Crystal, 2007 and birds (Goto & Watanabe, 2012;Inman & Shettleworth, 1999;Roberts et al 2009;Teller, 1989) have provided inconclusive evidence supporting a claim of metacognitive abilities in some experiments. In other experiments, rats (Kirk, McMillan, & Roberts, 2014;Templer, Lee, & Preston, 2017) and birds (Castro & Wasserman, 2013;Roberts, McMillan, Musolino, & Cole, 2012;Watanabe & Clayton, 2016) do appear to show responding consistent with a hypothesis of influence by a metacognitive system using the information-seeking paradigm or an uncertainty response.…”
Section: Limited Success In Metacognition Tests In Non-primate Speciesmentioning
confidence: 99%
“…This may also partly explain unnecessary searching in capuchin monkeys. Beran and Smith (2011) assessed information seeking using a computerized task with capuchin monkeys and rhesus macaques and contrasted performances with published pigeon results (Roberts et al, 2009). The primary task was a matching-to-sample task with three comparison options.…”
Section: The Curious Case Of Capuchin Monkeys As a Meaningful Failurementioning
confidence: 99%
“…Although the initial findings of Roberts et al (2009) failed to yield evidence of information seeking in pigeons, the new experimental designs and procedures used by Zentall and Stagner (2010) and in the new study reported here indicate that pigeons will respond for information that can be used to obtain reward. In both cases, equalizing the delay to reinforcement for informative and non-informative choices seems to yield a preference for the informative choice.…”
Section: Of the Circle Led Directly To Test Stimuli (Experiments 1a) mentioning
confidence: 92%
“…Experiments with pigeons were carried out in our laboratory to address this question (Roberts, Feeney, McMillan, Macpherson, Musolino, & Petter, 2009). The procedure was similar to that described for testing monkeys in the Beran and Smith (2011) studies.…”
Section: Do Pigeons Show Information Seeking?mentioning
confidence: 99%
“…The aim was to investigate whether animals would choose to go directly to the test or to study a sample stimulus before trying to choose the shape that matched the sample. To obtain this information the animal had to touch a "reveal samples" icon (pigeons: Roberts et al, 2009;capuchins and rhesus monkeys: Beran and Smith, 2011). In another memory test, initially developed in pigeons by Roberts et al 2009, subjects could get a reminder when memory of the sample was weak.…”
Section: Evaluation Of Metacognitive Control: the Hint-seeking Paradigmmentioning
confidence: 99%